Pelatihan Desain Media Promosi Sebagai Upaya Membekali Lulusan Smk Barunawati Menyonsong Dunia Kerja - Siswo Martono; Mochammad Arifin; Fenty Fatminnansih; Setya Putri Erdiana (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2023)
Not all SMK Barunawati alumni continue to higher education, the school management are fully aware that their students don't have appropriate skills to get into society. The purpose of this community service activity is to provide additional skills to Barunawati Vocational High School students in promotional media design. Training activities are implemented using lecture methods, tutorials and mentoring. The results are measured by 4 indicators, 1) the ability to use Canva as design applications, 2) The ability to make product visualization sketches, 3) The ability to present product information, 4) The ability to create creative promotional content. Each indicator has an increasing average value. The highest score indicator is the ability to design creative promotional media with score 3.7, while the lowest indicator is the ability to make product visualization sketches. In general, the response of participants to this training was very good, hopefully there will be follow-up with further level training. Promotional media design training equips participants to get involved in society.